Ionic liquid-tolerant cellulase from palm kernel cake for efficient lignocellulose hydrolysis - Elgharbawy, Amal Ahmed; Alam, Md. Zahangir; Jamal, Parveen; Moniruzzaman, Md. (2015)
Palm kernel cake (PKC) was utilized as the main media for cellulase enzyme production using solid-state bioconversion (SSB). The fermentation was carried out for 7 days using Trichoderma reesei with 0.05% Tween-80 and moisture content of 62.0% (w/w). The enzyme was extracted with citrate buffer (pH 4.8) at 150 rpm agitation speed. The enzyme extract was centrifuged and then purified by ultrafiltration membrane. The activity of the cellulase was determined by carboxymethyl cellulose (CMC) assay at 72.45 Unit/ml (603.75 U/ g of dry PKC). The PKC-cellulase (PKC-Cel) was tested in several ionic liquids (ILs) for its compatibility and stability as a combined system and the residual activity was calculated by taking the IL-free enzyme as the control (100%). The ionic liquids were: choline acetate (CoAc), 1-ethyl-3-methylimidazolium acetate (EMIMAc), dimethylimidazolium dimethylphosphate 90.45±0.44% of its activity in the concentration of 10.0, 20.0 and 40.0% of the (IL/citrate buffer) solution, where at 60.0 and 80.0%, 76.66±2.46 activity was retained. At a concentration of 100%, 63.16±0.04 of the initial activity was maintained for a duration of 6 hours. On the other hand, at 100% of EMIMAc, PKC-Cel could only sustain 4.75±0.2315% of the initial activity. In contrast, 95.62±0.68% was maintained in EM- DEP in concentration varied at 10, 20 and 40% of the (IL/buffer) whereas 36.03±0.46% remained in the pure IL. In DM-DMP, PKC-Cel was stable with no loss of its activity at 10.0, 20.0 and 40% for the first 3 hours, retaining only 8.17±0.28% of its activity after 6 hours.